Literature Review: Universal Design for Learning (UDL) Approach of Chemistry Learning in Inclusion Schools - Nurramadhani, Aisyah Zahra; Pratama, Kiki Putri Septya; Amelia, Lisa; Kusuma, Aldi; Erika, Farah (Universitas Pendidikan Mandalika, 2024)
Inclusive education is a promising way to create an equitable and high-quality education system that accepts all learners, including those with special needs. Universal Design for Learning (UDL) offers a flexible and dynamic approach to meet the various needs of learners, helping them to reach their full potential in education. This literature study aims to discover the application of the universal design for learning approach in chemistry learning. The research method used Narrative Literature Review (NLR), which uses the Google Scholar database to search for journal articles from the last ten years. The results of the literature show that applying the Universal Design for Learning approach in chemistry learning has a major influence in improving the learning experience and learning outcomes of students with special needs. Various interesting teaching materials such as learning videos, interactive games, and the application of E-modules are also used to support the learning process.